A Comparison of Risk Factors Among Discharged Military Veterans and Civilians Involuntarily Hospitalized Under California's Sexually Violent Predator Act. (September 2021) - Paden, Sarah G.; Azizian, Allen; Sreenivasan, Shoba; McGuire, Jim; Brooks Holliday, Stephanie; Seto, Michael C.
While military veterans have a lower overall rate of incarceration for criminal offenses than civilians, they have a higher rate of incarceration for violent sexual offenses. Despite military veteran overrepresentation among individuals adjudicated for violent sexual offenses, little is known about their risk factors for sexual offending. This study compared military veterans and civilians who had been involuntarily hospitalized and discharged pursuant to California's Sexually Violent Predator Act. Pedophilic disorder appeared nearly twice as often among veterans than civilians (62.7% vs. 38.7%), whereas antisocial personality disorder was twice as common among civilians compared to veterans (48.1% vs. 23.9%). Consistent with the result for pedophilic disorder, veterans were more likely to target male victims age 13 and below, while civilians tended to target female victims over the age of 13. The results suggest different risk profiles for veterans compared to civilians who have been convicted of sexually violent offenses.